Hunting the falcon : Henry VIII, Anne Boleyn, and the marriage that shook Europe - Guy, John, 1952 November 17-; Fox, Julia (Harper, an imprint of HarperCollinsPublishers, 2023)
Based on new research, this history of Henry VIII's courtship, short union, and brutal execution of Anne Boleyn provides dispels previously held myths about Boleyn's role in the marriage.